Rapid diagnostic tests for malaria - Theodoor Visser; Jennifer Daily; Nora Hotte; Caitlin Dolkart; Jane Cunningham; Prashant Yadav (The World Health Organization, 2015)
Maintaining quality, competitiveness and innovation in global health technology is a constant challenge for manufacturers, while affordability, access and equity are challenges for governments and international agencies. In this paper we discuss these issues with reference to rapid diagnostic tests for malaria. Strategies to control and eliminate malaria depend on early and accurate diagnosis. Rapid diagnostic tests for malaria require little training and equipment and can be performed by non-specialists in remote settings. Use of these tests has expanded significantly over the last few years, following recommendations to test all suspected malaria cases before treatment and the implementation of an evaluation programme to assess the performance of the malaria rapid diagnostic tests. Despite these gains, challenges exist that, if not addressed, could jeopardize the progress made to date. We discuss recent developments in rapid diagnostic tests for malaria, highlight some of the challenges and provide suggestions to address them.